Respons Pertumbuhan Bibit Kelapa Sawit dengan Pemberian Kompos Pelepah, Tandan Kosong Kelapa Sawit, dan Air Cucian Beras - Ariyanti, Mira; Firma, Farin Gelsbrata; Rosniawaty, Santi; Suherman, Cucu (Jurnal Agro Industri Perkebunan, 2022)
In oil palm plantations, compost application for plants aims to support a sustainable cropping system. The study aimed to determine the effect of oil palm midrib compost, oil palm empty fruit bunches and rice washing water on the growth of oil palm seedlings in the main nursery. The experiment was conducted at the Ciparanje Experimental Garden, Faculty of Agriculture, Padjadjaran University, from February 2020 to August 2020. The experiment was conducted using an experimental method using a randomised block design consisting of twelve treatments with three replications. The treatments included the application of inorganic fertilisers, oil palm midrib compost, oil palm empty fruit bunch compost and rice washing water either singly or in a combination of the three. Observations were made on the variables of increase in plant height, increase in stem girth, increase in the number of palm midribs, and leaf chlorophyll content. The F (Fisher) test analysed observational data at a 95% confidence level, followed by Duncan's multiple range test at a 95% confidence level. Data analysis using the SASM-Agri application. A mixture of 1.600 g of oil palm midrib compost, 100 g of oil palm empty fruit bunch compost with 500 ml of rice washing water can be used as a reference for the composition of organic fertiliser for oil palm seedlings, especially its effect on the increase of stem girth and leaf chlorophyll content.